(untitled) (American Journal of Islam and Society, 2011)
A New Introduction to Islam is an excellent undergraduate textbook presenting a thorough history of Islam. It introduces students to the history and development of Islamic studies as a discipline—showing how Islamic studies has shaped our understanding of Islam—and it also examines how the vibrant religious culture of the Near East produced a unique and brilliant intellectual and religious tradition spanning the fields of Islamic law, theology, philosophy, and mysticism. In addition, it shows the ways in which the Islamic tradition has enriched the world, and in turn, how it has been enriched by interaction with other civilizations. And against the background of social and cultural contexts that extend from North Africa to South and Southeast Asia, it also considers the opportunities and challenges facing Muslims today and provides a new and illuminating perspective of the development of Muslim beliefs and practices ...